A6.18 Novel compound cytokine release inhibitory drug 3 (CRID3) inhibits the NLRP3 inflammasome in rheumatoid arthritis. (13th February 2015) - McGarry, T; Coll, RC; Robertson, AAB; Cooper, MA; O'Neill, LA; Veale, DJ; Fearon, U
Abstract : Background/Objectives: The NLRP3 inflammasome is a multi-protein complex activated in response to environmental pathogens. These pathogens activate toll-like receptors, initiating a cascade leading to the activation of this inflammasome which results in caspase-1-dependant cleavage of pro-IL-1β and IL-18 to their active and mature form. Recent studies have implicated the NLRP3 inflamamsome is the pathogenesis of Rheumatoid Arthritis. This study demonstrates the effect of novel inhibitory compound CRID3 in the RA joint. Methods: To assess if the NLRP3 inflammasome is active in RA, the expression of inflammasome components NLRP3, IL-1β, IL-18 and Caspase-1 were measured in Rheumatoid Arthritis (RA) and Osteoarthritis (OA) ex vivo synovial tissue biopsies by RT-PCR, ELISA and immunohistochemistry. RA synovial explant cultures ex vivo were cultured under basal conditions or in the presence of CRID3 (100 nM), a novel compound which is thought to act on or closely to NLRP3. Expression of NLRP3, IL-1β, IL-18 and Caspase-1 in synovial explant cultures were analysed by Taqman PCR, ELISA and Western blotting. Furthermore, the effect of CRID3 on spontaneous secretion of pro-inflammatory and pro-angiogenic mediators (IL-6, IL-8, TNFα, VEGF, Tie-2, bFGF, MMP-3, IL-10) from RA explants was determined by ELISA or MSD multiplex assay. Results: Transcripts of inflammasome components pro-IL-1β, pro-IL-18 and NLRP3 were significantly higher in RA versus OA synovial biopsies (all p < 0.05). In addition, Caspase-1 is highly expressed in RA synovial tissue compared to healthy control synovium, localised to the lining and sub-lining layers. Incubation of ex vivo RA synovial explants with CRID3 decreased NLRP3 transcripts, pro-IL1β and pro-IL-18, which was mirrored by a decrease in spontaneous secretion of active IL-1β and IL-18 (all p < 0.05). CRID3 also inhibited Caspase-1 expression in RA explant cultures. Pro-inflammatory cytokines IL-6 and IL-8 were also significantly inhibited following incubation with CRID3 (p < 0.05). In contrast, CRID3 had no effect on other pro-inflammatory/angiogenic mediators – TNFα, MMP-3, VEGF, Tie-2, bFGF and IL-10. Conclusion: CRID3, thought to interact with the NLRP3 inflammasome, inhibits NLRP3 inflammasome components IL-1β, IL-18 and Caspase-1, in addition to other pro-inflammatory cytokines in the joint, but is independent of TNFα. This is the first study to demonstrate the effects of CRID3 in RA patient tissue and may represent a novel therapeutic strategy.